STRATEGI IMPLEMENTASI BUDAYA SEKOLAH INKLUSI RAMAH ANAK BAGI SISWA TUNADAKSA: STUDI KASUS DI SDN 1 TUNJUNGAN BLORA - Hubaibi Kirom Mujahidin; Liftiah; Ali Formen (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the strategies and implementation of an inclusive child-friendly school culture for students with physical disabilities (diplegia) at SDN 1 Tunjungan, Blora. Using a qualitative case study approach, data were collected through observation, in-depth interviews with the classroom teacher, and documentation of one fourth-grade student with hand motor impairments and articulation difficulties. The results show that the implemented strategies include modified writing tools (pencil with foam grip), seating arrangement in the front row, peer assistance, and extended time for completing assignments. However, challenges persist due to the absence of special assisting teachers, speech therapy, assistive technology (speech-to-text), and physical accessibility facilities (ramps, handles). The inclusive culture is still at an early stage, but the teacher's caring professional identity and peer empathy are positive assets. This study recommends ongoing teacher training, multi-stakeholder collaboration, and provision of adaptive facilities to build a sustainable inclusive school culture.